Measuring the sun depression angle of Dawn with a DSLR camera - Kassim Bahali,; Abdul Latif Samian,; Nazri Muslim,; Nurul Shazana Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The first visibility of the dawn occurs at a definite angle of the sun depression, Do which is used to calculate the fajr (dawn) prayer time. Dawn observations were carried out using Digital Single-lens Reflex (DSLR) camera in the period from February to December 2017 at several locations in both Malaysia and Indonesia (Lat. between 2.0° - 7.0° N, Long. 95.0°-106.0°E). Within the observational period, 64 days of the dawn luminance at horizon were recorded with backgrounds of both sea and land. The purpose of these observations was to determine the sun depression angle Do at the first moment when the dawn is seen using a DSLR camera. The results indicated that Do can be determined using a DSLR camera. The value of Do is between -14.5° and -18.5° with a mean value of -16.67° and standard deviation of 0.9992. This suggests that the new sun depression angle Do for dawn prayer is -17.0°.